Ancillary Obligations as an Additional Obligation of a Limited Liability Company’s Member - Marjanski, Vladimir (Zbornik radova Pravnog fakulteta u Novom Sadu, 2017)
Ancillary obligation can be defined as an obligation of a limited liability company’s member undertaken through the instrument of incorporation, which can take the form of monetary or non-monetary obligation (usually it is an obligation of a non-monetary character), which has a certain financial value and can be the object of a legally valid obligation. Ancillary obligations, as a contribution to activities of the company, are not regulated in the Law on Companies. The legal nature of this obligation is different from the obligation to make a contribution in money or in kind to a company’s assets, to make additional pay-ins or from the landing of funds to the company. Ancillary obligation is an optional and additional obligation of a limited liability company’s member and the obligation itself and its contents is defined in the instrument of incorporation. When a limited liability company’s member undertakes an ancillary obligation this creates a distinctive relationship between the member and the company, concerning their respective obligations and the legal status of the company, as well as certain consequences derived from those obligations.